Developmental mRNA m5C landscape and regulatory innovations of massive m5C modification of maternal mRNAs in animals - Liu, Jianheng; Huang, Tao; Chen, Wanying; Ding, Chenhui; Zhao, Tianxuan; Zhao, Xueni; Cai, Bing; Zhang, Yusen; Li, Song; Zhang, Ling; Xue, Maoguang; He, Xiuju; et al. (Nature communications, 2022)
m 5 C is one of the longest-known RNA modifications, however, its developmental dynamics, functions, and evolution in mRNAs remain largely unknown. Here, we generate quantitative mRNA m 5 C maps at different stages of development in 6 vertebrate and invertebrate species and find convergent and unexpected massive methylation of maternal mRNAs mediated by NSUN2 and NSUN6. Using Drosophila as a model, we reveal that embryos lacking maternal mRNA m 5 C undergo cell cycle delays and fail to timely initiate maternal-to-zygotic transition, implying the functional importance of maternal mRNA m 5 C. From invertebrates to the lineage leading to humans, two waves of m 5 C regulatory innovations are observed: higher animals gain cis-directed NSUN2-mediated m 5 C sites at the 5' end of the mRNAs, accompanied by the emergence of more structured 5'UTR regions; humans gain thousands of trans-directed NSUN6-mediated m 5 C sites enriched in genes regulating the mitotic cell cycle. Collectively, our studies highlight the existence and regulatory innovations of a mechanism of early embryonic development and provide key resources for elucidating the role of mRNA m 5 C in biology and disease. mRNAs are known to be decorated with m5C at a low-to-medium level. Here, the authors generate atlases of mRNA m5C during animal development in 6 species and identify convergent and unexpected massive methylation of maternal mRNAs by NSUN2 and NSUN6.